Implementation of the Labuan Hospital Revitalization Policy as a Public Service Facility - Humaeroh, Siti; Permatasari, Neng Hani (MID Publisher International, 2025)
The Regional Public Hospital (RSUD) plays a crucial role in providing essential healthcare services to the community. However, in several regions, its performance remains suboptimal, necessitating revitalization policies to enhance service effectiveness and equity. This study aims to analyze the implementation of the revitalization policy of RSUD Labuan conducted by the Banten Provincial Government as an effort to improve public service quality in the health sector. The research employs a qualitative descriptive approach using data collection techniques such as observation, interviews, and document study, with informants selected through purposive sampling. Data analysis was carried out using an interactive model consisting of data reduction, data display, and conclusion drawing. The results indicate that the implementation of the RSUD Labuan revitalization policy has not been fully optimal. The main obstacles are found in the aspects of communication, resources, disposition, and bureaucratic structure, as described by Edward III’s policy implementation theory. It is suggested that better inter-agency coordination, sufficient resource allocation, and institutional governance strengthening are needed to achieve sustainable revitalization outcomes.